Dança, ludicidade e educação inclusiva no Centro de Referência em Educação Infantil Professor Orlando Bitar em Belém - PA - MELO, Kerollen Pinheiro de (2024)
The present study arises from the curricular component Teaching Internship I, of the Degree in Dance course at UFPA, developed at the Reference Center for Early Childhood Education Prof. Orlando Bitar – CREI Orlando Bitar, in Belém-PA. This production is supported by Normative Instruction No. 01/2023 PROEG/UFPA, which provides in an exceptional and temporary manner on the academic guidelines for the standardization and carrying out of the activities of the Course Completion Work - TCC, making its form of preparation, presentation and defense, due to the consequences arising from the COVID-19 pandemic; as regards art. 4th, paragraph I, which concerns the preparation of a scientific article. The objective was to analyze the teaching-learning process through Dance of a child with Autism Spectrum Disorder - ASD and a child with Attention Deficit Hyperactivity Disorder - ADHD, from the perspective of playfulness. One of the practices used as a form of stimulation for children with disabilities are playful activities, including games, toys and games, singing toys, oral narratives, among others. The research was developed through a qualitative approach with a focus on action research guided by the perspective of Inclusive Education. The research instruments were: observation, practical activities and conversation circles. The result of the study showed that the inclusion of children with disabilities in the school context promotes socialization and stimulates creative, motor, cognitive and affective development through playful activities that stimulate their development in a pleasurable and fun way, enabling the construction of meaningful and comprehensive knowledge, which can corroborate the its autonomy.